Dual Energy X-ray Absorptiometry (DEXA) as a longitudinal outcome measure of cancer-related muscle wasting in mice - Cole, Calvin L.; Beck, Christopher A.; Robinson, Deja; Ye, Jian; Mills, Bradley; Gerber, Scott A.; Schwarz, Edward M.; Linehan, David (PloS one, 2020)
Pancreatic ductal adenocarcinoma (PDAC) is notorious for its associated skeletal muscle wasting (SMW) and mortality. Currently, the relationships between PDAC, SMW, and survival are poorly understood. Thus, there is great need for a faithful small animal model with quantitative longitudinal outcome measures that recapitulate clinical PDAC, to define SMW onset and assess progression. Therefore, we aimed to validate dual energy X-ray absorptiometry (DEXA) as a longitudinal measure of lean mass, and demonstrate its utility to quantify SMW in the KCKO murine model of PDAC. In vivo body composition of: 1) untreated mice at 5, 8, 12, 18, and 22 weeks of age (n = 4) and 2) a cohort of mice with (n = 5) and without PDAC (n = 5), was determined via DEXA and lean mass of the lower hind limbs was predicted via a region of interest analysis by two-independent observers. Total body weight was determined. Tibialis anterior (TA) muscles were weighed and processed for histomorphometry immediately post-mortem. Statistical differences between groups were assessed using ANOVA and Student's t-tests. Linear regression models and correlation analysis were used to measure the association between TA and DEXA mass, and reproducibility of DEXA was quantified via the intraclass correlation coefficient (ICC). Lean mass in growing untreated mice determined by DEXA correlated with TA mass (r2 = 0.94; p <0.0001) and body weight (r2 = 0.89; p <0.0001). DEXA measurements were highly reproducible between observers (ICC = 0.95; 95% CI: 0.89-0.98). DEXA and TA mass also correlated in the PDAC cohort (r2 = 0.76; p <0.0001). Significant SMW in tumor-bearing mice was detected within 38 days of implantation, by DEXA, TA mass, and histomorphometry. DEXA is a longitudinal outcome measure of lean mass in mice. The KCKO syngeneic model is a bona fide model of PDAC associated SMW that can be quantified with longitudinal DEXA.